Usulan Model Pemeliharaan Distribusi Tenaga Listrik Menggunakan Metode TRDX Untuk Meningkatkan Keandalan Pada Pelanggan Industri - Musthopa Musthopa; Budi Harsanto; Akhmad Yunani (Universitas Mercu Buana, 2021)
Reliability of electricity supply is urgently needed by modern industry because disruptions can directly impact production levels, costs and company profitability. The purpose of this study is to determine the characteristics of the existing maintenance of electric power distribution to industrial customers of PT PLN (Persero) UP3 Karawang and to propose appropriate maintenance methods to improve its performance. The method used is a case study with data collected through observation, interviews, and analysis of relevant documents. The results of the study indicate that the trend of feeder disturbances during 2017-2020 has not met expectations, the realization of the average interruption frequency index (SAIFI) system continues to increase in succession 3.12; 3.85; 5.47; and 6.92 times/customer, as well as the realization of the system average interruption duration index (SAIDI) with an increasing trend, respectively, 182.97; 314.31; 1015.55; and 612 minutes/customer. The three highest causes of disturbances were jointing (39%), followed by third party causes (36%) and cubicle damage (15%). The author proposes the TRDX method to improve the reliability of electric power supply to industrial customers.